Technical «living book» and advanced network technologies - Nikolay A. Balonin; M. B. Sergeev (Moscow Polytechnic University, 2022)
In the paper the future of technical books is analyzed. The process of establishment of advanced network technologies that change the idea of a book, especially a technical book, isconsidered. A new concept of the modern technical book, containing pages with executable algorithms and provided with the link to described objects, is proposed.